An analysis of conflict managements used by félicie in the movie leap! (2016) - Umul, Dewi Sartika; Resen, I Wayan; Karya, I Wayan Sidha (Journal of Language and Applied Linguistics, 2020)
This research entitled An Analysis of Conflict Managements used by Félicie in the Movie Leap! (2016) aims to analyze types of conflict management used by the main character to overcome the conflict in the movie Ballerina/Leap. The data source of this research is the movie Leap! (2016) which was published in 2016 as the result of the collaboration of Quad Production, Caramel Film, and Main Journey in 2016 and directed by Eric Warin and Eric summer. The data is was collected through documentation method, by Watching the movie repeatedly, and then the data is identified and selected the data that is used in this research. The collected data is analyzed qualitatively and presented descriptively. A theory that is used in this research is proposed by Rahim (2002) about conflict management. Based on the research, it shows that all types of conflict management proposed by the expert are used by Félicie, the main character in this movie Leap! (2016). There are five occurrences in total, namely Integrating, Obliging, Dominating, Avoiding, and Compromising.